PENGENALAN APLIKASI OBYEK WISATA TELAGA NGEBEL BERBASIS VIRTUAL REALITY DAN ALGORTIMA GREEDY - Bhanu Setyawan, Mohammad; Permana Putra, Angga Dian; Sussolaikah, Kelik; Zulkarnain, Ismail Abdurrozaq; Cobantoro, Adi Fajaryanto (Jurnal Media Elektro, 2024)
Ngebel Lake in Ponorogo Regency is a tourist destination that is usually visited by many local or non-local tourists. There is great potential to be developed again to introduce this tourist attraction to outside the region in order to attract tourists. Telaga Ngebel requires the main role of promotion and publication out, so it is very necessary for a technology that is able to realize the equal introduction of Telaga Ngebel attractions and is able to describe tourist objects in real terms. The solution is to utilize Virtual Reality technology that can package the potential of tourist attractions in an attractive, attractive and contemporary manner. The technology displays Telaga Ngebel attractions in 3600 with a 3-dimensional object model and the nearest wahan search feature using the Greedy Algorithm with a virtual reality display. In its preparation using SDLC (Software Development Life Cycle). The final result of making this application in the form of Virtual Reality Telaga Ngebel and also games using the greedy algorithm used as an implementation of games that present the charm of Telaga Ngebel. Based on the results of usability test research with the SUS method obtained a score of 51 or in adjective OK criteria.